A comprehensive risk stratification at early follow-up determines prognosis in pulmonary arterial hypertension. (1st June 2017) - Kylhammar, David; Kjellström, Barbro; Hjalmarsson, Clara; Jansson, Kjell; Nisell, Magnus; Söderberg, Stefan; Wikström, Gerhard; Rådegran, Göran
Abstract: Aims: Guidelines recommend a goal-oriented treatment approach in pulmonary arterial hypertension (PAH). The aim is to reach a low-risk profile, as determined by a risk assessment instrument. This strategy is incompletely validated. We aimed to investigate the bearing of such risk assessment and the benefit of reaching a low-risk profile. Methods and results: Five hundred and thirty PAH patients were included. Follow-up assessments performed after a median of 4 (interquartile range 3–5) months were available for 383 subjects. Patients were classified as 'Low', 'Intermediate', or 'High risk' and the benefit of reaching the 'Low risk' group was estimated. Survival differed ( P < 0.001) between the risk groups at baseline and at follow-up. Survival was similar for patients who remained in or improved to the 'Low risk' group. Survival was similar for patients who remained in or worsened to the 'Intermediate risk' or 'High risk' groups. Irrespective of follow-up risk group, survival was better ( P < 0.001) for patients with a higher proportion of variables at low risk. Results were unchanged after excluding patients with idiopathic PAH >65 years at diagnosis, and when patients with idiopathic or connective tissue disease-associated PAH were analysed separately. Patients in the 'Low risk' group at follow-up exhibited a reduced mortality risk (hazard ratio 0.2, 95% confidence interval 0.1–0.4 in multivariable analysis adjusted for age, sex and PAH subset), as compared to patients in the 'Intermediate risk' or 'High risk' groups. Conclusion: These findings suggest that comprehensive risk assessments and the aim of reaching a low-risk profile are valid in PAH.